AB0221 ADA2 Deficiency: Description of a New Mutation for a Surprising Phenotype. (9th June 2015) - Uettwiller, F.; Rodero, M.; Sarrabay, G.; Marot, Y.; Quartier, P.; Crow, Y.
Abstract : Background: Autosomal recessive loss of function mutations in CECR1 encoding adenosine deaminase 2 (ADA2) were newly reported to cause early-onset stroke and inflammatory vasculoapthy with polyarteritis nodosa as pathological feature. Overexpression of interferon stimulated genes (ISGs) has been suggested as part of the physiopathology and neutrophil related genes signature has been described in some patients. Objectives: To describe the clinical and genetic features of two siblings; to measure ADA2 activity, secretion of inflammatory cytokines, interferon signature and expression of neutrophil related genes. Methods: Double stranded DNA sequencing (NM_00128225.1) was performed. ADA2 activity in serum was assessed using a commercial kit. Methods for the assessment of the expression of a panel of ISGs and neutrophil stimulated genes have been previously published and validated. Cytokine secretion was assessed by ELISA. Results: We report the case of a 9 years old girl of non consanguineous parents presenting at the age of 3 years with fever, systemic inflammation, lesions of cutaneous vasculitis and inflammatory muscles lesions. Muscular biopsy fund focal necroziting angeitis of a minor interfascicular artery compatible with a periarteritis nodosa. The girl experienced neurological ischemic transient attack with mild lymphocytic pleocytosis in the cerebrospinal fluid and two strokes leaving here with spasticity and a diminution of her mental performances. MRI showed pedoncular and mesencephalic lesions. She was resistant to steroids, cyclosporine and azathioprine. Pulses of cyclophosphamid allowed a transient clinical remission but she presented once more an aggravation and we decided to move to antiTNF (etanercept) Her sister was followed for anemia since age of one year, with mild unexplained inflammatory syndrome. She had no cutaneous or muscular expression and no fever. At the age of 3, she presented with transient paralysis of the third cranial nerve. At the age of 5, she presented with transient vestibulitis. Both were considered as viral but cerebral MRI revealed a lacunar stroke. Double stranded DNA sequencing showed an biallelic mutation: p.Tyr453Cys, already published and known to be pathogen by prediction analysis and a deletion of exon 6 predicted to shift the reading frame. ADA2 activity showed a significant reduction compared to control. In the two cases, interferon related genes signature was significantly elevated. Neutrophil genes showed no increased expression. Inflammatory cytokines were not significantly oversecreted. Conclusions: We describe here a new mutation with a surprising clinical picture of the youngest girl: start in a very young age with no cutaneous expression, no fever and two transient neurological events. Association of inflammatory syndrome even mild with neurological unexplained event must lead to test for ADA2 mutation. ADA2 activity is probably not linked to the phenotype, as already suggested. If some patients seem to have a neutrophil signature with remarkable response to antiTNF, some are not, perhaps consistent with different sub classes of ADA2 deficiency. New therapeutics targeting the interferon pathways could be a novel approach to try. Disclosure of Interest: None declared